2018
DOI: 10.3390/su10093018
|View full text |Cite
|
Sign up to set email alerts
|

Governing the Moral Hazard in China’s Sponge City Projects: A Managerial Analysis of the Construction in the Non-Public Land

Abstract: As a new development mode for solving urban water control problems, a sponge city has been widely concerned and steadily promoted in China. The source engineering in the non-public land is called a low-impact development system. Although it is an important part of a sponge city, the effect of its construction and operation is not ideal at present. The main reason for this lies in the moral hazard behavior of the developer who is the responsible party and the agent. In this research, governance mechanisms for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Jehan (2021) also recognized that risk is a big concern for anyone contemplating investing in new, especially innovative ventures and suggested an alternative venture investment approach called diminishing Musharakah (DM) which has roots in Islamic modes of investment and is more suited for ventures with a higher risk profile because it focused on four key ingredients, due diligence, flexibility, moral hazard reduction, and risk reduction. Specifically, as a new development mode for solving urban water control problems, and a sponge city has been widely concerned and steadily promoted in China, governance mechanisms for preventing the moral hazard behavior are put forward (Ma et al 2018). Therefore, to obtain higher yields, farmers may excessively use pesticides when they grow crops, causing moral hazard behavior ,which showed that Chinese traditional culture has a positive effect on ameliorating the farmers' excessive use of pesticides in crop production (Zhang and Li, 2016) .Similarly, Katz (2016) took water policies in Israel as an example and showed that a type of moral hazard phenomenon by which consumers, aware of the increases in potential supply, discount the importance of conservation.…”
Section: Moral Hazardmentioning
confidence: 99%
“…Jehan (2021) also recognized that risk is a big concern for anyone contemplating investing in new, especially innovative ventures and suggested an alternative venture investment approach called diminishing Musharakah (DM) which has roots in Islamic modes of investment and is more suited for ventures with a higher risk profile because it focused on four key ingredients, due diligence, flexibility, moral hazard reduction, and risk reduction. Specifically, as a new development mode for solving urban water control problems, and a sponge city has been widely concerned and steadily promoted in China, governance mechanisms for preventing the moral hazard behavior are put forward (Ma et al 2018). Therefore, to obtain higher yields, farmers may excessively use pesticides when they grow crops, causing moral hazard behavior ,which showed that Chinese traditional culture has a positive effect on ameliorating the farmers' excessive use of pesticides in crop production (Zhang and Li, 2016) .Similarly, Katz (2016) took water policies in Israel as an example and showed that a type of moral hazard phenomenon by which consumers, aware of the increases in potential supply, discount the importance of conservation.…”
Section: Moral Hazardmentioning
confidence: 99%
“…Agency theory and stewardship theory are contrasting theories about CEO behavioral intentions (Martin and Butler 2017 ). Under agency theory, the agent who engages in economic activities will make maximum efforts to improve their own effectiveness while the principal will bear the cost if things go poorly (Ma et al 2018 ). While agency doctrine depicts top managers as individualistic, opportunistic, and self-serving, steward doctrine depicts top managers as collectivist, pro-organizational, and trustworthy (Davis et al 1997 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Agency theory builds on economic utilitarianism and self-interest, and presents that information asymmetry and goal conflict pose governance challenges. In such a case, the agent who engages in economic activities will make maximum efforts to improve their own effectiveness while the principal will bear the cost if things go badly (Ma et al , 2018). Contractual incentives are commonly used to guide the agent's behavior in order to minimize the potential for the agency problems of moral hazard and adverse selection (Toivonen and Toivonen, 2014).…”
Section: Theoretical Backgroundmentioning
confidence: 99%